Menentukan Harga Kain Katun Menggunakan Fuzzy Inference System Metode Mamdani - Lim, Louis; Rinaldo, Rinaldo; Lee, Lesley Peterson; Sherly, Sherly; Yulianto, Andik (Telcomatics, 2024)
Entrepreneurs must keep up with technological developments to compete in an increasingly competitive business environment. This competition causes price fluctuations that affect sales, requiring the right decisions for business survival. Cotton fabric is highly favored by consumers in the textile industry. The success and failure of this business depends on pricing. Setting a selling price too high may cause customer dissatisfaction, while setting a price too low may cause business losses. Therefore, determining an optimal selling price is crucial. Adopting fuzzy logic is proposed as a solution for this problem. Fuzzy logic can be applied to predict the selling price of cotton fabrics. This test aims to determine the selling price of cotton cloth by making a Fuzzy Inference System (FIS) using the Mamdani method with variables of material quality, production method, design, and coloring method as considerations. The results of this test show that the comparison of the system made by manual calculation and simulation with Python has an error rate of 0,00019% calculated by MAPE. Based on the results, this system is useful as an auxiliary tool in making decisions because it is able to overcome uncertainty in determining the selling price of cotton fabric.